Functional impairments of elderly in rural areas of east Sikkim, India: cross-sectional study - Engheepi, Frieda Bokali P.; Sonowal, Nikita Joshi; Mehta, V. K.; Rai, Ajoy Daniel (International Journal Of Community Medicine And Public Health, 2018)
Background: Ageing is a universal, biological reality, which affects every individual on this earth.India, being the second largest country with 8.4% of the total population belonging to the age group of 60 years and above faces challenges of population ageing. The major concern now being the health care of the elderly as functional ability decreases with age leading to avoidance of challenging situations, restricted activity and further decline in health. The objective of this study was to find out the functional impairments of elderly in rural areas of East Sikkim using Lawton’s instrumental activities of daily living scale. Methods: Cross-sectional study was carried out with 324 elderly people aged 60 years and above. The study sample was obtained using multistage random sampling method. Out of total 52 GPU’s in rural areas of east Sikkim, 18 GPU’s were selected using random generation number method and then the list of all the elderly were obtained from each selected GPU. From this list, 18 elderlies in each GPU were randomly selected for the study thus the total sample size was 324. The study was conducted using Lawton’s instrumental activities of daily living (IADL) scale. Results: There was significant difference between the IADL score of both the genders (p=0.0001). There was no significant relationship in IADL score with age (r=-0.072). However, 2.5% of the elderly were totally dependent for IADL activity. Conclusions: Developing multidisciplinary approaches for improving quality of life might be a fruitful approach in elderly and thus enhancing the policy makers for forming a comprehensive geriatric rehabilitation services to provide health care accessibility for every elderly.